2010
DOI: 10.1021/la904194a
|View full text |Cite
|
Sign up to set email alerts
|

Detergent Effects on Membranes at Subsolubilizing Concentrations: Transmembrane Lipid Motion, Bilayer Permeabilization, and Vesicle Lysis/Reassembly Are Independent Phenomena

Abstract: Soluble amphiphiles, or detergents, are known to produce a number of structural and dynamic effects on membranes, even at concentrations below those causing membrane solubilization (i.e. in the so-called stage I of detergent-membrane interaction). The main subsolubilizing detergent effects on membranes are transmembrane lipid motion (flip-flop), breakdown of the membrane permeability barrier (leakage), and vesicle lysis/reassembly. For a proper understanding of membrane solubilization by detergents, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 42 publications
(83 reference statements)
6
51
0
1
Order By: Relevance
“…Furthermore, since the tail tip morphology defect is correlated with the 15°C growth arrest in most experiments, it is likely that this phenotype also is due to a defect in desaturase regulation. We were intrigued by the possibility of rescuing the paqr-2 mutant by using detergents at concentrations expected to increase membrane fluidity [28], [29]. Strikingly, we found that small amounts of Nonidet P-40 or Triton X-100 are excellent at rescuing the tail tip morphology at 20°C and the growth at 15°C (Figure 8A–B and Figure S5A–B).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, since the tail tip morphology defect is correlated with the 15°C growth arrest in most experiments, it is likely that this phenotype also is due to a defect in desaturase regulation. We were intrigued by the possibility of rescuing the paqr-2 mutant by using detergents at concentrations expected to increase membrane fluidity [28], [29]. Strikingly, we found that small amounts of Nonidet P-40 or Triton X-100 are excellent at rescuing the tail tip morphology at 20°C and the growth at 15°C (Figure 8A–B and Figure S5A–B).…”
Section: Resultsmentioning
confidence: 97%
“…Fluorescence measurements were performed by setting the (ANTS + DPX) emission at 520 nm and the excitation at 355 nm. The 0% leakage corresponded to the fluorescence intensity ( F 0 ) of a suspension containing 100 μM liposomes at time zero; 100% leakage was the fluorescence value ( F 100 ) obtained when LUV are lysed by adding 10 μl Triton X-100 [ 24 ]. To test the destabilizing effect of lead the metal was added to liposomal suspensions at different concentrations.…”
Section: Liposome Membrane Permeabilitymentioning
confidence: 99%
“…A different approach to enhance the permeability of the liposomal membranes and, hence, modulate the enzymatic activity is to make use of lipid/detergent hybrid membranes since the addition of detergents to vesicles composed of phospholipids leads to an increase in the permeability of the membrane . Although detergent‐induced permeabilization of phosphatidylcholine‐based liposomes had been studied in the past, Treyer et al were the firsts to study the effect of detergents on the diffusion of molecules through the liposomes membrane in the context of encapsulated enzymatic reactions.…”
Section: Micro/nanosized Single‐compartment Enzymatic Reactorsmentioning
confidence: 99%